Against all odds: exhaustive activation in lexical access of verb complementation options. Issue 9 (20th October 2016) - Shetreet, Einat; Linzen, Tal; Friedmann, Naama
ABSTRACT: Various findings suggest that once a verb is accessed, all of its complementation options are activated. This fMRI study examined whether all the complementation options are activated even in contexts where this seems unnecessary. We examined whether introducing the selected complement prior to the verb (in topicalised sentences) still involves the activation of all complementation options. We performed ROI analyses in the left STG, a brain region that has been linked to the processing of argument structure and the number of complementation options. In this region, multiple-option verbs elicited greater activations compared with one-option verbs, both when the complement appeared after the verb and when it appeared pre-verbally. This suggests encapsulated lexical retrieval of the verb, which involves exhaustive activation of all its complementation options when the verb is accessed.